2019
DOI: 10.1177/1077801219853367
|View full text |Cite
|
Sign up to set email alerts
|

It Won’t Happen to Me: An Examination of the Effectiveness of Defensive Attribution in Rape Victim Blaming

Abstract: Defensive attribution posits that victim blame results from one’s underlying perception of vulnerability. The resulting blame is believed to reduce perceived similarity to the victim and vulnerability to victimization, though extant research has neglected to examine its effectiveness in men and women. The current study employed multigroup analysis structural equation modeling with 618 male and female undergraduates exposed to fictional police reports of a reported rape. The theory was partially supported; amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The results also demonstrate that women were more victim blaming than the men, and this victim blaming was related in part by faulty beliefs that the victim asked for or wanted sexual intercourse. These results are consistent with previous research supporting the role of defensive attribution of victim blame (Pinciotti & Orcutt, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The results also demonstrate that women were more victim blaming than the men, and this victim blaming was related in part by faulty beliefs that the victim asked for or wanted sexual intercourse. These results are consistent with previous research supporting the role of defensive attribution of victim blame (Pinciotti & Orcutt, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…The collective adaptation to violent behaviours and resulting learned helplessness increases the perceived need to restore safety/control and regulate anxiety to maintain psychological integrity. In an attempt to resolve this cognitive dissonance (Festinger, 1957 ) subjects tend to exaggerate individual characteristics or behaviour as the primary reasons for victimhood (attitude change; McGrath, 2017 ), especially when defending their assumption of a just world or safety (Dawtry, Callan, Harvey, & Gheorghiu, 2020 ; Lerner, 1980 ; Pinciotti & Orcutt, 2019 ; Walster, 1966 ). In a meta-analysis with 55 experimental studies, Dawtry et al ( 2020 ) confirmed that victims were rated less favourable when presenting with greater and more authentic suffering, or when harm went unpunished.…”
Section: Trauma and The Communitymentioning
confidence: 99%
“…Research has consistently supported Shaver’s DAT, with females displaying self-protective distortion repeatedly in order to minimize the perceived possibility that such an incident could happen to them, “harm avoidance”, and to avoid the possibility of being blamed should they encounter the same situation, “blame avoidance” (Pinciotti & Orcutt, 2019; Shaw & McMartin, 1973). Particularly, Pinciotti and Orcutt (2019) explained that defensive attribution postulates that victim blame is caused by one’s underlying perception of vulnerability and the resulting blame tends to reduce perceived similarity to the victim and vulnerability to victimization. Both sexes could be a victim and affected, but women are mostly blamed when compared to their men counterparts.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Defensive attributions predict negative victim perception to decrease as the similarity of the observer to the victim increases, this being a defense mechanism to protect the observer from being blamed themselves if a similar fate should befall them in the future. Research has consistently supported Shaver’s DAT, with females displaying self-protective distortion repeatedly in order to minimize the perceived possibility that such an incident could happen to them, “harm avoidance”, and to avoid the possibility of being blamed should they encounter the same situation, “blame avoidance” (Pinciotti & Orcutt, 2019; Shaw & McMartin, 1973). Particularly, Pinciotti and Orcutt (2019) explained that defensive attribution postulates that victim blame is caused by one’s underlying perception of vulnerability and the resulting blame tends to reduce perceived similarity to the victim and vulnerability to victimization.…”
Section: Theoretical Frameworkmentioning
confidence: 99%